On a class of limit distributions in Hilbert space - Kruglov, B. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: М. Круглов. Об одном классе предельных распределений в гильбертовом пространстве V. Kruglovas. Apie vieną ribinių pasiskirstymų klasę Hilberto erdvėje